anonymous
  • anonymous
2x-y=3, 7x-3y=12 substution method
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
AkashdeepDeb
  • AkashdeepDeb
@uri You aren't substituting there! :)
uri
  • uri
lol
anonymous
  • anonymous
would y be 3 as well?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

uri
  • uri
@terenzreignz Am i wrong..
terenzreignz
  • terenzreignz
No... but the instructions *clearly* say 'use substitution'...
AkashdeepDeb
  • AkashdeepDeb
You eliminated there! :)
uri
  • uri
Ow.
terenzreignz
  • terenzreignz
Try it again @uri ^_^
uri
  • uri
Le doing accounting homework. :p
terenzreignz
  • terenzreignz
You and your excuses... Anyway, @drea83 Your first step is to pick an equation (first one recommended) and isolate one of the variables (y recommended).
anonymous
  • anonymous
uri , can you write the question with system ?
anonymous
  • anonymous
Do you know system ?
anonymous
  • anonymous
When we have x & y use that
anonymous
  • anonymous
Look :!
AkashdeepDeb
  • AkashdeepDeb
Do this... FOR SUBSTITUTION STEP 1: Find the value of any variable in terms of the other variable in the first equation. STEP 2: 2x-y=3 y = 2x - 3 STEP 3: NOW substitute this variable's value in the second equation. STEP 4: 7x-3y=12 7x - 3(2x-3) = 12 7x - 6x + 9 = 12 Get x's value. ^_^ [Learnt that from @terenzreignz ] STEP 5: Put x's value in the first equation to get the y value. :D Understood? :)
nirmalnema
  • nirmalnema
2x-3=y and 7x-3y=12 so u get y=2x-3 from the 1st eq.. replace its value in the 2nd eq.. so u get 12=7x-3(2x-3) 12=7x-6x+9 x = 3 put in the 1st eq u will get y = 3
AkashdeepDeb
  • AkashdeepDeb
@drea83 Understood this? :D
anonymous
  • anonymous
2x-y=3 7x-3y=12 ___________________________________________________________________________________ 7 . (2x -y = 3) 2 . (7x-3y=12) _____________________________________________________________________________________- And now we want find y s first so shold x1= -(x2) ______________________________________________________________________________ so we have : 14x - 7y =21 14x - 6y =24 _________________________________________________________________________________ Now we should kill x s so reduse them : but we dont have : x1= -(x2) so do it by (-1) ___________________________________________________________________________________-- -1 .( 14x - 7y =21) ___________________________________________________________________________________ so we have : -14x + 7y =-21 14x-6y=+12 ______________________________ then reduse them from them ! -14x+7y =-21 14x -6y =12 __________________ y =-9 ________________________________________________________ Y = -9 Now can you find X ? Do you under stand ?

Looking for something else?

Not the answer you are looking for? Search for more explanations.